2006
DOI: 10.1161/01.atv.0000220108.97208.67
|View full text |Cite
|
Sign up to set email alerts
|

Biological Significance of Decreased HSP27 in Human Atherosclerosis

Abstract: Objective-Because culprit atherosclerotic plaques contain proteases, we hypothesized that the diminished heat shock protein 27 (HSP27) released by atherosclerotic plaques could be due to proteolysis. We assessed the role of HSP27 in human vascular smooth muscle cells (VSMCs) under proteolytic injury. Methods and Results-Active plasmin is present in culprit atherosclerotic plaques. Recombinant HSP27 was cleaved by plasmin and this effect was prevented by different inhibitors. Fragments and aggregated forms of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 32 publications
5
72
2
Order By: Relevance
“…Also, expression of a specific diphosphorylated form of HSP27 was present in healthy blood vessels as opposed to vessels with cardiac allograft vasculopathy in patients who had undergone cardiac transplantation (28 ). Recently, it was re- ported that intracellular HSP27 allowed protection against plasmin-induced anoikis in human vascular smooth muscle cells and was inversely localized with apoptotic cells within culprit atherosclerotic carotid plaques (29 ). The role of HSP27 in the extracellular compartment remains unclear; exogenously added HSP27 was shown to prevent neutrophil apoptosis (30 ) but did not have any effect on plasmin-induced apoptosis in vascular smooth muscle cells (29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, expression of a specific diphosphorylated form of HSP27 was present in healthy blood vessels as opposed to vessels with cardiac allograft vasculopathy in patients who had undergone cardiac transplantation (28 ). Recently, it was re- ported that intracellular HSP27 allowed protection against plasmin-induced anoikis in human vascular smooth muscle cells and was inversely localized with apoptotic cells within culprit atherosclerotic carotid plaques (29 ). The role of HSP27 in the extracellular compartment remains unclear; exogenously added HSP27 was shown to prevent neutrophil apoptosis (30 ) but did not have any effect on plasmin-induced apoptosis in vascular smooth muscle cells (29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was re- ported that intracellular HSP27 allowed protection against plasmin-induced anoikis in human vascular smooth muscle cells and was inversely localized with apoptotic cells within culprit atherosclerotic carotid plaques (29 ). The role of HSP27 in the extracellular compartment remains unclear; exogenously added HSP27 was shown to prevent neutrophil apoptosis (30 ) but did not have any effect on plasmin-induced apoptosis in vascular smooth muscle cells (29 ). To our knowledge, 2 clinical studies of HSP27 and atherosclerosis have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…As previously described, incubation of vascular tissue ex vivo for 24 h in serum-free culture medium is compatible with proteomic analysis and provides valuable information on the vessel wall secretome by comparing various experimental conditions (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…To confirm our hypothesis that plasma content can reflect arterial wall secretion, we showed that circulating concentrations of HSP27 were decreased in subjects with atherosclerosis, indicating that this protein could be a novel biomarker of atherosclerosis in relation to healthy subjects. The biological significance of decreased HSP27 plasma levels in human atherosclerosis has been recently described [35]. Based on observations showing that culprit atherosclerotic plaques contain proteases [36,37], we hypothesized that the decreased HSP27 released by atherosclerotic plaques could be caused by proteolysis of the protein.…”
Section: The Secretome Of Atheroma Plaquesmentioning
confidence: 96%
“…Based on observations showing that culprit atherosclerotic plaques contain proteases [36,37], we hypothesized that the decreased HSP27 released by atherosclerotic plaques could be caused by proteolysis of the protein. This extracellular degradation of HSP27 in atherosclerotic plaques could reflect a pathological vascular remodeling process, in which the final balance between proteases and antiproteases favors the degradative process of the ECM [35]. Controlled clinical trials in well-defined clinical populations will be necessary to evaluate the predictive value of all these candidate proteins as there is currently limited evidence of their usefulness in clinical practice.…”
Section: The Secretome Of Atheroma Plaquesmentioning
confidence: 99%